Human resources management: a contemporary model for principles of Free State schools - Griesel, Johan David (University of the Free State, 2004)
The purpose of this study was to investigate the human resources management task of the school principal in the Free State Province. In order to achieve this goal, research was done regarding the human resources management task of school principals, which forms part of their complex overall management task. The research entails a literature study to investigate human resources management in practice and also to focus on the functioning thereof in schools as a management task of the school principal. The human resources management task of the school principal and the various management areas which it covers were grouped under human resources provision and human resources maintenance. In Chapter 2 human resources provision was discussed according to the following areas of management: human resources planning, recruitment, selection, placement, induction and career management. In Chapter 3 the maintenance of human resources was discussed according to the following areas of management: training and development, performance appraisal, compensation, motivation, quality of work life, leadership, groups, labour relations, health and safety, and administration. Furthermore, an empirical investigation was undertaken to determine the way in which school principals approach and execute their human resources management task. In Chapter 4 frequency tables were utilised to obtain more information regarding the day-to-day management of human resources in schools by school principals. The continuation of the empirical research in Chapter 5 aimed at determining the training needs of school principals, as well as ascertaining the level of importance of specific human resources management tasks in the opinion of school principals. Various subgroups were identified beforehand and comparisons were made further to clarify the research. The empirical research undeniably proved that school principals have a definite training need with regard to human resources management and that they view these management tasks as highly significant as seen against the background of their total management task at school. In Chapter 6 a model was drawn up with regard to human resources management based on the literature study and the empirical research. The goal of this model is to serve as a guideline for school principals in the execution of their management task with regard to human resources management. In the final chapter certain findings were formulated regarding the human resources management task of school principals. Furthermore certain recommendations were made to illustrate to the Free State Department of Education that definite training needs exist which will empower school principals for their management tasks; and the attention of school principals was drawn to the importance of their management task with regard to the management of human resources in schools in order to realise the education and teaching goals of schools

Die doel van hierdie studie was om die menslikehulpbronnebestuurstaak van die skoolhoof in die Vrystaat Provinsie te ondersoek. Ten einde hierdie doel te bereik, is navorsing gedoen rakende die menslikehulpbronnebestuurstaak van die skoolhoof, wat deel vorm van sy/haar komplekse oorkoepelende bestuurstaak. Die navorsing het bestaan uit ‘n literatuurstudie om menslikehulpbronnebestuur in die praktyk te ondersoek en ook om die funksionering daarvan in skole as ‘n bestuurstaak van die skoolhoof toe te lig. Die menslikehulpbronnebestuurstaak van die skoolhoof en die onderskeie bestuursareas waaruit dit bestaan, is gegroepeer onder menslikehulpbronnevoorsiening en menslikehulpbronneversorging. In Hoofstuk 2 is menslikehulpbronnevoorsiening onder die volgende bestuursareas bespreek: menslikehulpbronnebeplanning, werwing, seleksie, plasing, induksie en loopbaanbestuur. In Hoofstuk 3 is die versorging van menslikehulpbronne bespreek na aanleiding van die volgende bestuursareas: opleiding en ontwikkeling, prestasie-beoordeling, vergoeding, motivering, kwaliteit van werkslewe, leierskap, groepe, arbeidsverhoudinge, gesondheid en veiligheid, en administrasie. Verder is ‘n empiriese ondersoek onderneem om te bepaal hoe skoolhoofde hul menslikehulpbronnebestuurstaak benader en uitvoer. In Hoofstuk 4 is hoofsaaklik deur middel van frekwensie tabelle gepoog om meer inligting te bekom rakende die dag-tot-dag bestuur van menslikehulpbronne in skole deur skoolhoofde. Met die voortsetting van die empiriese navorsingsverloop in Hoofstuk 5 was die doel om die opleidingsbehoeftes van skoolhoofde met betrekking tot hul menslikehulpbronnebestuurstaak te bepaal en ook om die belangrikheid van bepaalde menslikehulpbronnebestuurstake in die oë van skoolhoofde vas te stel. Onderskeie sub-groepe is vooraf geïdentifiseer en onderlinge vergelykings is getref om die studie verder toe te lig. Die empiriese navorsingsverloop het onteenseglik bewys dat skoolhoofde ‘n besliste opleidingsbehoefte het met betrekking tot menslikehulpbronnebestuur en dat hulle hierdie bestuurstake as baie belangrik teen die agtergrond van hul totale bestuurstaak in skoolverband beskou. In Hoofstuk 6 is ‘n model met betrekking tot menslikehulpbronnebestuur gegrond op die literatuurstudie en die empiriese navorsingsverloop saamgestel. Die doel van hierdie model is om as riglyn te dien vir skoolhoofde in die uitvoering van hul bestuurstaak met betrekking tot menslikehulpbronnebestuur. In die laaste hoofstuk is bepaalde bevindinge rakende die menslikehulpbronnebestuurstaak van skoolhoofde geformuleer. Verder is sekere aanbevelings gedoen om die Vrystaatse Onderwysdepartement daarop te wys dat definitiewe opleidingsbehoeftes bestaan om skoolhoofde beter vir hul bestuurstaak toe te rus en skoolhoofde is attent gemaak op die belangrikheid van hul bestuurstaak met betrekking tot die bestuur van menslike hulpbronne in skole ten einde die opvoedings- en onderrigdoelwitte van skole te verwesenlik.
Thesis (Ph.D. (Comparative Education and Education Management))--University of the Free State, 2004
Keywords: Education district; Educator; Free State Department of Education; Free State Province; Human resources; Human resources maintenance; Human resources management; Human resources provision; Importance of human resources management tasks; Non-educator; School principal; Training needs; School personnel management -- South Africa -- Free State; School principals -- South Africa -- Free State; Educational leadership -- South Africa -- Free State; School management and organization -- South Africa -- Free State